ONLINE LEARNING MOTIVATION DURING COVID-19 PANDEMIC - Shee Mun Yong; Lip Sam Thi (UUM Press, 2022)
Purpose - Due to the COVID-19 pandemic, the Malaysian government declared a Movement Control Order (MCO) to prevent the spread of the virus. Educational institutions were forced to switch their pedagogy to online learning to complete the semester curriculum, catching academicians and students off-guard that resulted in makeshift online lesson delivery. Previous online learning motivation studies have neglected the impact of an unplanned or sudden transition to online learning during a pandemic on student motivation to learn. This study aims to examine location learning environment, learner-instructor interactions, and self-efficacy of students more succinctly on their learning motivation during an unplanned transition to online learning. Method - This study used a sequential explanatory mixed method strategy with a sample size of 535 randomly collected from a public and two private higher education institutions in Malaysia. IBM SPSS statistical software v22 was used for descriptive statistics. Regression testing was carried out using AMOS statistical software v21 structural equation modeling. Findings - Revealed the importance of location learning environment in fostering student motivation and the positive influence of learner-instructor interactions on students achieving the desired learning outcomes during an unplanned transition to online learning. However, there is no evidence to suggest a causal effect between student self-efficacy and online learning motivation during such conditions. The theoretical implication indicates that having conducive hygiene factors are essential to driving student motivation under such situations. Significance - The COVID-19 pandemic provides opportunities for researchers to examine the role of various motivational theories to explain student motivation in learning under challenging conditions. Educators and students would benefit on ways to increase student online learning motivation in lockdown conditions. Setting up a more efficient online delivery approach could lead to higher student satisfaction and potential enrolment.